Sustainability performance, ownership structures, and corporate financial stability of shariah-compliant companies in Malaysia / Mohamad Azwan Md Isa, Norashikin Ismail and Mohd Halim Kadri - Md Isa, Mohamad Azwan; Ismail, Norashikin; Kadri, Mohd Halim (Universiti Teknologi MARA, Perlis, 2025)
The launching of the United Nation’s SDGs Agenda 2030 in 2015 has boosted sustainability practices among the corporate sectors. Since then, the studies related to corporate sustainability practices and financial performance have gained extensive interest among researchers and academics. Nonetheless, studies on the association between sustainability performance (SUSP) and corporate financial stability (CFS) are still scarce and the results remain inconclusive. Therefore, this study aimed to examine the association between the SUSP and CFS focusing on the Shariah-compliant companies in Malaysia. In addition, this study attempted to investigate the moderating roles of different forms of ownership structures on the SUSP-CFS nexus. Using balanced panel data from 2021 to 2023, the Fixed Effect models as suggested by the Hausman test, indicate that the SUSP has mixed association with CFS. In addition, concentrated ownership has a negative but insignificant influence on the CFS whilst managerial ownership shows positive but insignificant influences on the CFS. In terms of moderating roles, concentrated ownership indicates a weakening effect on the SUSP-CFS association whilst managerial ownership poses a strengthening effect on the SUSP-CFS association. This study benefits the management of companies, investors and policymakers as well as enriching the body of knowledge on sustainability-financial stability literature. The corporate sectors need to sustainability practices through ESG initiatives in their strategic planning. The investors have to support the corporate sustainability practices by taking into account the sustainability factors in their investment decisions. Policymakers are to play more attentive roles in encouraging the corporate sectors in their sustainability practices by providing efficient infrastructure, robust ESG frameworks, and effective incentive packages. With these concerted efforts, the global SDGs agenda can be materialized successfully besides ensuring the financial stability of the Shariah-compliant companies in Malaysia